Modern hotel operations management - Chibili, Michael N. (Noordhoff Uitgevers, 2016)
A comprehensive and wide-ranging introduction to operational hotel management, this textbook brings together business administration, management and entrepreneurship into a complete overview of the discipline. Essential reading for students of hospitality management, the book also benefits from online support materials including student tests, a glossary and PowerPoint slides.--Provided by publisher.